Bhutto and The Breakup of Pakistan - Yunus, Mohammed (Karachi Oxford University Press, 2011)
The bifurcation of Pakistan resulting in the emergence of Bangladesh in December 1970 was a decisive and irreversible event in the short history of Pakistan that has received much academic and journalistic attention. It was a painful time for the people of Pakistan who were rudely awakened from a dream. Slowly the gloom lifted in what is Pakistan today as the unsavoury facts and reasons for the disaster came to light. The author watched the country slip through the fingers of its people from a sensitive spot in the government of those days. Not everything, however, came into the public view particularly the thought and conduct of the rulers that remained secret. That information belongs to the people of Pakistan and the historians who take interest in them. A part of that information has long laid dormant with the author. Time has now come to unveil it for the scrutiny and comment of those who would like to complete the picture."
Include Appendix, Epilogue and Index.
Keywords: India-Pakistan Conflict, 1971. -- Pakistan -- Foreign Relations -- 1947-1971.